Initiating the action of wildlife conservation through local custom and regulation in Singgalang village Tanah Datar West Sumatra - Azwir Anhar; Reki Kardiman (Pelita Eksakta, 2026)
There are national regulations on conservation of wildlife in Indonesia, but the implementation has not been optimum due to lack of monitoring by the government. This program was trying to initiate local participative on conservation of wildlife, specifically initiating a village constructing their own regulation or local custom for sustainable natural resources management. The program was conducted in Singgalang village Tanah Datar Regency West Sumatra, with multi local stakeholders belong to customary holders, tourism leading group, the official village staffs, women association and schools across the village were involved. The program was officially openned by vice Bupati of Tanah Datar Regency, then it was followed by seminar with Yayasan SINTAS Indonesia for biodiversity richness and the problems, and completed by PAGARI for local custom implementation. The participants were excited with the seminar and took various necessary messages. This provided great insight to let the local stakeholders create their local custom